2014
DOI: 10.2139/ssrn.2503210
|View full text |Cite
|
Sign up to set email alerts
|

Crop Diversification, Economic Performance and Household's Behaviours: Evidence from Vietnam

Abstract: This study examines economic performances and household '

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
2
2
0
Order By: Relevance
“…Results are however, in contrast with the findings of [11] who reported that specialization impacts negatively on productivity of smallholder farmers in Papua New Guinea. [1,11,12,16,25,28] also reported in the same line. Their findings revealed that diversification impacts positively on the TEs of vegetable-based cropping systems in South Africa, tomato production in Oyo (Nigeria), small-scale dry season vegetable farmers in Sokoto (Nigeria), peasant farmers in Nigeria, and multiple crop farmers in Vietnam respectively.…”
Section: Estimates Of the Magnitude Of Technical Efficiencies Of Survsupporting
confidence: 67%
“…Results are however, in contrast with the findings of [11] who reported that specialization impacts negatively on productivity of smallholder farmers in Papua New Guinea. [1,11,12,16,25,28] also reported in the same line. Their findings revealed that diversification impacts positively on the TEs of vegetable-based cropping systems in South Africa, tomato production in Oyo (Nigeria), small-scale dry season vegetable farmers in Sokoto (Nigeria), peasant farmers in Nigeria, and multiple crop farmers in Vietnam respectively.…”
Section: Estimates Of the Magnitude Of Technical Efficiencies Of Survsupporting
confidence: 67%
“…Makate et al (2016) argued that diversified cropping systems primarily reduce crop production risks by providing more income options to the farmer, therefore, making production on the farm more stable. Our finding that more diversified farms are more efficient is consistent with Nguyen (2014), Manjunatha et al (2013), Ogundari (2013), Rahman (2009) and Coelli and Fleming (2004) for Vietnam, India, Bangladesh, Nigeria and Papua New Guinea, respectively.…”
Section: Empirical Results and Discussionsupporting
confidence: 91%
“…Kidane and Zegeye (2018) contended that management of crop diversification is complex and requires appropriate skills and input as compared to specialized production. In Vietnam, Nguyen (2014) established a substantial inefficiency resulting from multiple crop production, which causes production loss of close to 20%. However, this finding contrasts with the study by Bangwayo-Skeete et al (2012).…”
Section: Resultsmentioning
confidence: 99%